The In Vitro Immunomodulatory Effects of Gold Nanocomplex on THP-1-Derived Macrophages - Duaa Abuarqoub; Nouf N. Mahmoud; Rand Zaza; Rana Abu-Dahab; Enam A. Khalil; Dima A. Sabbah (Journal of Immunology Research, 2022)
Introduction. This study is aimed at investigating the immunological response after treating THP-1 cells with gold nanorods conjugated with a phosphatidylinositol 3-kinase (PI3Kα) inhibitor. Methodology. Gold nanorods were synthesized and functionalized with cholesterol-PEG-SH moiety, and the treatment groups were as follows: nanocomplex (a drug-conjugated gold nanorods), free drug (phosphatidylinositol 3-kinase (PI3Kα) inhibitor), and GNR (the nanocarrier; cholesterol-coated gold nanorods). THP-1 cells were differentiated into macrophages and characterized by measuring the expression of macrophage surface markers by flow cytometry. Then, differentiated cells were activated by lipopolysaccharide (LPS). Afterwards, activated macrophages were treated with the different treatments: nanocomplex, free drug, and GNR, for 24 hrs. After treatment, the production of the inflammatory cytokines measured at gene and protein levels by using qPCR and CBA array beads by flow cytometry. Results. Our results show that THP-1 cells were successfully differentiated into macrophages. For inflammatory cytokine expression response, nanocomplex and free drug showed the same expression level of cytokines at gene level, as the expression of IL-1β, IL-6, and TNF-α was significantly downregulated (p<0.0005, p<0.0005, p<0.00005), respectively, while IL-8, IL-10, and TGF-β were all upregulated in a significant manner for nanocomplex (p<0.00005, p<0.00005, p<0.00005) and free drug treatment group (p<0.00005, p<0.05, p<0.05) compared to the control untreated group. While in the GNR group, IL-6 and TNF-α were downregulated (p<0.005, p<0.00005), and IL-12p40 (p<0.00005) was upregulated all in a statistically significant manner. While at protein level, cells were treated with our nanocomplex: IL-1β, IL-6, TNF-α, and IL-12p70 and were significantly decreased (p<0.00005,p<0.005,p<0.05,p<0.00005), and IL-10 was found to be significantly increased in culture compared to the untreated control group (p<0.005). For free drug; IL-1β and IL-12p70 were significantly decreased (p<0.00005, p<0.00005), while a significant increase in the secretion levels of IL-10 only was noticed compared to the untreated group (p<0.005). For GNR treatment groups, IL-1β, TNF-α, and IL-12p70 were significantly decreased (p<0.00005, p<0.05, p<0.00005). Conclusion. We can conclude that our nanocomplex is a potent effector that prevents tumoral progression by activating three main immunological strategies: switching the surface expression profile of the activated macrophages into a proinflammatory M1-like phenotype, downregulating the expression of proinflammatory cytokines, and upregulating the expression level of anti-inflammatory cytokines.